Double Cystic Duct: Preoperative use of MRCP Without Being Aware of the Anatomic Anomaly: A Case Report - Liang, Zhi; Chen, Junsheng; Liang, Yonggui; Wang, Jijun; Song, Xiaobiao (Frontiers in Surgery, 2022)
Introduction: A biliary anomaly is occasionally encountered, however, double cystic duct is exceedingly rare during surgery. It is pivotal for surgeons to recognize the anatomic variations in Cholangiography which performed under fluoroscopic guidance Intraoperatively to prevent possible complications. Case Presentation: Herein, the case of a 66-year-old female patient with acute cholecystitis, in which preoperative Magnetic Resonance Cholangiopancreatograph（MRCP）don't identify a single gallbladder with double cystic ducts, is presented. Intraoperatively we identified double cystic duct and it was safely ligated with clips. Anatomic variability was also confirmed by Cholangiography which performed under fluoroscopic guidance. Furthermore, the patient was symptom-free through 1 year of follow-up assessment. Conclusions: In particular, when we don't find anatomic variability based on imaging, cholangiography under fluoroscopic guidance during surgery was a powerful tool that may clearly show the anomaly of a single gallbladder with double cystic ducts.